Barriers and readiness for implementation of Indonesian sustainable palm oil in independent smallhollders plantations: A case study - Revi, Lestia (Holistic: Journal of Tropical Agriculture Sciences, 2025)
Background: Smallholders have been required to implement a sustainable system in developing their plantations. Sustainability aspects that have been determined by the government that must be obeyed and fulfilled by every smallholder are listed in the principles and criteria of Indonesian Sustainable Palm Oil (ISPO). This research will focus on how smallhodelrs preferring and implementation gap ISPO certification requirements, as well as what factors cause these gaps. Methods: Data was collected based on direct interviews with 11 Village Unit Cooperative Administrators (KUD) in Sanggau Regency. The data was then processed and studied using the Gap Analysis method. Findings: The average implementation of ISPO in the respondent cooperatives is only 37 percent, which means that there is no implementation of ISPO in in the practice of cultivating oil palm plantations by independent smallholders. Independent smallholders need special training in its implementation some of the factors that cause gaps in the implementation of ISPO in independent smallholders in Sanggau Regency include organizations that are not well developed, limited access to finance. Conclusions:  The lack of information obtained by independent smallholders regarding the principles and procedures for implementing ISPO, as well as the lack of socialization of sustainable oil palm cultivation practices from both government and private institutions. One of solution to that problems is need a patner organization who can collaborate to implementation ISPO in smallholders. Novelty: This research contributes to the limited studies on ISPO implementation among independent smallholders, particularly in Sanggau Regency. Unlike previous studies that focus on large-scale palm oil industries, this study provides empirical insights into the practical challenges faced by smallholders.